The genotypic false positive rate determined by V3 population sequencing can predict the burden of HIV-1 CXCR4-using species detected by pyrosequencing. - Valentina Svicher (Public Library of Science (PLoS), 2013)
Objective The false-positive rate (FPR) is a percentage-score provided by Geno2Pheno-algorithm indicating the likelihood that a V3-sequence is falsely predicted as CXCR4-using. We evaluated the correlation between FPR obtained by V3 population-sequencing and the burden of CXCR4-using variants detected by V3 ultra-deep sequencing (UDPS) and Enhanced-Sensitivity Trofile assay (ESTA). Methods 54 HIV-1 B-subtype infected-patients (all maraviroc-naïve), with viremia >10,000copies/ml, were analyzed. HIV-tropism was assessed by V3 population-sequencing, UDPS (considering variants with >0.5% prevalence), and ESTA. Results By UDPS, CCR5-using variants were detected in 53/54 patients, irrespective of FPR values, and their intra-patient prevalence progressively increased by increasing the FPR obtained by V3 population-sequencing (rho = 0.75, p = 5.0e-8). Conversely, the intra-patient prevalence of CXCR4-using variants in the 54 patients analyzed progressively decreased by increasing the FPR (rho = -0.61; p = 9.3e-6). Indeed, no CXCR4-using variants were detected in 13/13 patients with FPR>60. They were present in 7/18 (38.8%) patients with FPR 20-60 (intra-patient prevalence range: 2.1%-18.4%), in 5/7 (71.4%) with FPR 10-20, in 4/6 (66.7%) with FPR 5-10, and in 10/10(100%) with FPR<5 (intra-patient prevalence range: 12.1%-98.1%). Conclusions FPR by V3 population-sequencing can predict the burden of CXCR4-using variants. This information can be used to optimize the management of tropism determination in clinical practice. Due to its low cost and short turnaround time, V3 population-sequencing may represent the most feasible test for HIV-1 tropism determination. More sensitive methodologies (as UDPS) might be useful when V3 population-sequencing provides a FPR >20 (particularly in the range 20-60), allowing a more careful identification of patients harboring CXCR4-using variants.